2005
DOI: 10.1111/j.1527-3458.2005.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties, Central Nervous System Effects, and Potential Therapeutic Applications of Atipamezole, a Selective α2‐Adrenoceptor Antagonist

Abstract: Atipamezole is an alpha2-adrenoceptor antagonist with an imidazole structure. Receptor binding studies indicate that its affinity for alpha2-adrenoceptors and its alpha2/alpha1 selectivity ratio are considerably higher than those of yohimbine, the prototype alpha2-adrenoceptor antagonist. Atipamezole is not selective for subtypes of alpha2-adrenoceptors. Unlike many other alpha2-adrenoceptor antagonists, it has negligible affinity for 5-HT1A and I2 binding sites. Atipamezole is rapidly absorbed and distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 66 publications
2
84
2
1
Order By: Relevance
“…It is a relatively small structure with ϳ3000 neurons in the rat (Loughlin et al, 1986a) and, although these cells are considered homogenous with respect to their NAergic neurochemistry, they can be divided into several different subgroups based on cell morphology and efferent targets (Loughlin et al, 1986b;Berridge and Waterhouse, 2003;Aston-Jones, 2004). With respect to pain control, it is the descending projections to the spinal dorsal horn that have received the most attention (Jones, 1991;Millan, 2002;Pertovaara, 2006) and these are predominantly located in the ventral pole and in the subceruleus (Westlund et al, 1983;Howorth et al, 2009a;Bruinstroop et al, 2012). Previous studies have shown that focal stimulation (electrical and/or chemical) of the LC region can produce antinociceptive effects (Margalit and Segal, 1979;Jones and Gebhart, 1986b;Jones, 1991;West et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is a relatively small structure with ϳ3000 neurons in the rat (Loughlin et al, 1986a) and, although these cells are considered homogenous with respect to their NAergic neurochemistry, they can be divided into several different subgroups based on cell morphology and efferent targets (Loughlin et al, 1986b;Berridge and Waterhouse, 2003;Aston-Jones, 2004). With respect to pain control, it is the descending projections to the spinal dorsal horn that have received the most attention (Jones, 1991;Millan, 2002;Pertovaara, 2006) and these are predominantly located in the ventral pole and in the subceruleus (Westlund et al, 1983;Howorth et al, 2009a;Bruinstroop et al, 2012). Previous studies have shown that focal stimulation (electrical and/or chemical) of the LC region can produce antinociceptive effects (Margalit and Segal, 1979;Jones and Gebhart, 1986b;Jones, 1991;West et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The LC is proposed to play an important role in an endogenous descending pain control circuit (Jones, 1991;Millan, 2002;Pertovaara, 2006). Given that this NAergic circuit component appears to be functionally underactive in chronic neuropathic pain (Howorth et al, 2009b;Alba-Delgado et al, 2012;Hughes et al, 2013), we have been interested in exploring the nature of this deficit and developing strategies to augment its activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These anesthetics and reversing drugs are labeled for use in traditional livestock, but in most of the situations with wildlife the same drugs are legally used in off-label procedures. Dosages, clearance times, and tissue residue levels for some of the above drugs have been established for some domesticated species [1][2][3][4], however, tissue residues have not been established for these drugs when used in white-tailed deer (Odocoileus virginianus). The levels of drug residues in the tissues of game animals like deer and elk that might be consumed by the public after the drug injection could be of some possible public health concern.…”
Section: Introductionmentioning
confidence: 99%